2013
DOI: 10.1136/bmjopen-2013-004146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ocular fundus pathology with type 2 diabetes in a Chinese urban community as assessed by telescreening

Abstract: ObjectiveTo describe the telescreening model and assess the prevalence of ocular fundus pathology in patients with type 2 diabetes within a Chinese urban community.DesignCommunity-based cross-sectional study.SettingHealthcare centre of Fengyutan Community, Shenyang, China.ParticipantsA total 528 patients (287 females) with type 2 diabetes mellitus (DM) were randomly recruited using health files from the healthcare centre of Fengyutan community between 8 October and 20 November 2012.Main outcome measuresSigns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…In particular, a study by Liu et al in China trained GPs to take photographs, which were read by a reading centre. Recommendations were returned to the GP for communication to patients . In South Africa, a mobile screening program integrated into different existing diabetes clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a study by Liu et al in China trained GPs to take photographs, which were read by a reading centre. Recommendations were returned to the GP for communication to patients . In South Africa, a mobile screening program integrated into different existing diabetes clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Upper‐middle‐income countries had the most studies using fundus cameras, as well as an increased focus on identifying of DR risk and cases through primary care referrals. One study in China examined the possibility of structuring fundus camera examinations by general practitioners, while an initiative in South Africa reported a systematic national screening program; recommendations from both South Africa and Latin America, however, suggested that such programs may not be feasible in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study also reported the sight-threatening consequence of DR to be higher in the rural areas (14.2%) compared with the urban areas (6.3%). Liu et al 9 reported the prevalence of DR to be 14% in patients living in the Fengyutan Community of Shenyang city in north-east China.…”
Section: Introductionmentioning
confidence: 99%
“…15 CSME may cause permanent central blindness and occurs when leakage in the central retina disrupts photoreceptors. Timely treatment of CSME also dramatically reduces vision loss by up to 60%, 16,17 with greater efficacy using intravitreal injections of corticosteroids and anti-vascular endothelial growth factor medications. 18 The proportion of vision impairment caused by CSME versus proliferative DR has been reported to be approximately 2 to 1, but may vary depending on the population being screened.…”
Section: Rationale and Description Of Tmdrs Screeningmentioning
confidence: 99%